Control interno y su relación con la eficiencia administrativa-operativa de la empresa Banandino S.A., cantón Quevedo, primer semestre año 2013 - Romero Córdova, Carolina Elizabeth (2015)
This research aims to evaluate internal control and administrative-operating company processes to measure the efficiency of the activities of the company BANANDINO SA which has its plantations Via Buena Fè Km 5½, the same that is dedicated to the marketing and export of bananas. The research focuses primarily on internal control and its relationship with the administrative and operational efficiency first half 2013, "in order to ensure that activities are executed daily according to what is established laws, policies and procedures. The evaluation of internal control began with the preliminary visit to the plantations to a deeper understanding of the activities, then proceeded to visit satellite offices located in Valencia, and get the existing reality of the organizational system, allowing to set the guide for the preparation of this work. To fulfill the objectives surveys to administrative-operational area were conducted, interviews were developed to establish the analysis and results. COSO I, its five components allowed to have a larger internal situation of the company BANANDINO SA knowledge, and have a direct understanding of the risks in the company which negatively affect the daily activities applied. The results obtained in the evaluation of internal control Through his five components gives us confidence level (61.71%) moderate and high risk level (38.29%) of the company BANANDINO SA, to know the compliance objectives and consider the cost of production and utility boxes and finally by checking policies, laws and procedures a fulfillment of 41% was obtained this occurs because the company does not give know the policies to their employees and because they are not properly laid.